(untitled) (Asian Journal of Pharmaceutics (AJP), 2015)
Sustained release matrix tablets of indomethacin (IM) were developed by employing a relatively less used hydrophilic polymer badam gum and gelucires. The dissolution rate of IM is first improved by dispersing the drug in hydrophilic gelucire (50/13) and the dispersion is then embedded in the matrix of badam gum and hydrophobic gelucire (43/01). Different ratios of IM and gelucire (50/13) were employed, and the solid dispersions were prepared by melting and solvent methods. The dispersion prepared by employing solvent method resulted in much higher dissolving product than was possible with the melting method. The differential scanning calorimetry and infrared spectroscopy (IR) studies revealed that there are no interactions between IM and gelucire and the XRD studies indicated that the drug IM existed in amorphous state in gelucire dispersion. Matrix tablets were prepared by direct compression employing different proportions of badam gum and gelucire (43/01). The prepared tablets were found to be of optimum hardness, uniform weight and acceptable friability. The drug release was found to be dependent on the ratio drug: Gelucire in the solid dispersion and also on the proportion of the release retarding polymer employed – gelucire (43/01) or badam gum. The drug release data suggested that the release of the drug is the first order and is diffusion controlled